'Health-value': potential epidemiological criteria for health communication - Aline Guio Cavaca; Paulo Roberto Vasconcellos-Silva; Tatiana Breder Emerich; Edson Theodoro dos Santos-Neto; Adauto Emmerich Oliveira (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
The study aims to develop potencial priorities criteria for health communication ('health-value'), from the analysis of health policies and morbidity and mortality data of Espírito Santo (ES, Brazil). Documentary research was performed from 2011 and 2012 data. These data were collected in state health priority policies and health information systems, and they were ranked according to decreasing criterion causes of mortality, morbidity and notification, in addition to the coincidence of the disease in more than one policy selected. The `healthvalue' shows ideally priority morbid conditions in the media agenda of ES, such as: ischemic heart diseases, cerebrovascular diseases, pneumonia, cancer, tuberculosis, hanseniasis, schistosomiasis and dengue. It highlights the persistence of diseases related to poor socio-sanitary conditions, plus child and maternal mortality, syphilis in pregnant women, Aids, diabetes and pertussis. Thus, 'health-value' acts as a relevant criterion in publicization of public problems in order to create attention and guided debates in society.